The Role of Communication Management in Enhancing Reputation for Service Excellence: CV. Indonesian Publications - Tamamiyah, Lutfiyatut (Worldwide Research Publishing, 2026)
The growth of the journal publishing services industry in Indonesia has elevated organizational reputation as a critical success factor. In this trust-based sector, reputation is shaped by the quality of communication throughout the service process. This study examines the role of communication management in building and sustaining a reputation for service excellence at CV. Indonesian Publications. A qualitative case study design was employed with three purposively selected informants: a communication manager, an editorial staff member, and a student service user. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive model of data analysis. The company demonstrates effective external communication during client onboarding, generating positive initial perceptions. However, delays in follow-up communication and inconsistent response speed during manuscript processing present reputational risks. Internally, coordination across editorial, technical, and customer service teams is managed through digital platforms and regular evaluations, though workload imbalances periodically disrupt responsiveness. Adaptive, proactive, and relationship-oriented communication systems are essential to sustaining organizational reputation. Synergy between internal and external communication constitutes the primary determinant of client trust and long-term loyalty in the academic journal publishing services sector.